The impact of loneliness and social isolation during COVID-19 on cognition in older adults: a scoping review - Kassam, Kareena; McMillan, Jacqueline M. (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic required implementation of public health measures to reduce the spread of SARS CoV-2. This resulted in social isolation and loneliness for many older adults. Loneliness and social isolation are associated with cognitive decline, however, the impact of this during COVID-19 has not been fully characterized. Objective The aim of this scoping review was to explore the impact of social isolation and loneliness during COVID-19 on cognition in older adults. Eligibility criteria Eligible studies occurred during the COVID-19 pandemic, enrolled older adults and reported longitudinal quantitative data on both loneliness (exposure) and cognition (outcome). Sources of evidence A comprehensive search was conducted in CINAHL, Medline, PubMed, and Psychinfo databases (updated October 10, 2023). Charting methods Studies were screened independently by two reviewers and study characteristics, including participant demographics, loneliness and cognition measurement tools, study objectives, methods and results were extracted. Results The search yielded 415 results, and seven were included in the final data synthesis. All studies were conducted between 2019 and 2023. Six studies enrolled community-dwelling individuals while the remaining study was conducted in long-term care. In 6 studies, loneliness and/or social isolation was correlated with poorer cognitive function. In the seventh study, subjective memory worsened, while objective cognitive testing did not. Conclusion Loneliness and social isolation during COVID-19 were correlated with cognitive decline in older adults. The long-term effect of these impacts remains to be shown. Future studies may focus on interventions to mitigate the effects of loneliness and social isolation during future pandemics.